Simon & Schuster children$1 (Bs guide to insects and spiders s - Johnson, Jinny; Simon and Schuster, inc. (New York, N.Y. : Simon & Schuster Books for Young Readers, 1996)
Provides an introduction to more than 100 insects and arachnids, giving general information about family characteristics and habits, and more specific facts about some species.
Includes index.
Keywords: Insects -- Juvenile literature; Spiders -- Juvenile literature; Insects